A Combined Strategy to Improve the Development of a Coral Antivenom Against Micrurus spp. - de Castro, Karen Larissa Pereira; Lopes-de-Souza, Letícia; de Oliveira, Daysiane; Machado-de-Ávila, Ricardo Andrez; Paiva, Ana Luiza Bittencourt; de Freitas, Cláudio F.; Ho, Paulo Lee; Chávez-Olórtegui, Carlos; Guerra-Duarte, Clara (Frontiers in Immunology, 2019)
Accidents involving Micrurus snakes are not the most common ones but are noteworthy due to their severity. Victims envenomed by Micrurus snakes are at high risk of death and therefore must be treated with coral antivenom. In Brazil, the immunization mixture used to fabricate coral antivenom contains Micrurus frontalis and Micrurus corallinus venoms, which are difficult to be obtained in adequate amounts. Different approaches to solve the venom limitation problem have been attempted, including the use of synthetic and recombinant antigens as substitutes. The present work proposes a combined immunization protocol, using priming doses of M. frontalis venom and booster doses of synthetic B-cell epitopes derived from M. corallinus toxins (four three-finger toxins-3FTX; and one phospholipase A2-PLA2) to obtain coral antivenom in a rabbit model. Immunized animals elicited a humoral response against both M. frontalis and M. corallinus venoms, as detected by sera reactivity in ELISA and Western Blot. Relevant cross-reactivity of the obtained sera with other Micrurus species (Micrurus altirostris, Micrurus lemniscatus, Micrurus spixii, Micrurus surinamensis) venoms was also observed. The elicited antibodies were able to neutralize PLA2 activity of both M. frontalis and M. corallinus venoms. In vivo, immunized rabbit sera completely protected mice from a challenge with 1.5 median lethal dose (LD50) of M. corallinus venom and 50% of mice challenged with 1.5 LD50 of M. frontalis venom. These results show that this combined protocol may be a suitable alternative to reduce the amount of venom used in coral antivenom production in Brazil.